2014
DOI: 10.1002/hep.26592
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 inflammasome activation results in hepatocyte pyroptosis, liver inflammation, and fibrosis in mice

Abstract: Inflammasome activation has been recently recognized to play a central role in the development of drug-induced and obesity-associated liver disease. However, the sources and mechanisms of inflammasome mediated liver damage remain poorly understood. Our aim was to investigate the effect of NLRP3 inflammasome activation on the liver using novel mouse models. We generated global and myeloid cell specific conditional mutant Nlrp3 knock-in mice expressing the D301N Nlrp3 mutation (ortholog of D303N in human NLRP3) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
671
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 777 publications
(701 citation statements)
references
References 43 publications
22
671
0
8
Order By: Relevance
“…Another unresolved question is whether the NLRP3 inflammasome activation occurs at the level of resident cells, since results so far obtained from preclinical models of obesity and insulin resistance are quite contrasting. There is good evidence that both hematopoietic and nonhematopoietic cells are involved in NLRP3 inflammasome activation in both renal and hepatic tissues (38)(39)(40)(41). The above data provide evidence in support ) and standardized to the corresponding β-actin contents.…”
Section: Discussionsupporting
confidence: 59%
“…Another unresolved question is whether the NLRP3 inflammasome activation occurs at the level of resident cells, since results so far obtained from preclinical models of obesity and insulin resistance are quite contrasting. There is good evidence that both hematopoietic and nonhematopoietic cells are involved in NLRP3 inflammasome activation in both renal and hepatic tissues (38)(39)(40)(41). The above data provide evidence in support ) and standardized to the corresponding β-actin contents.…”
Section: Discussionsupporting
confidence: 59%
“…Total RNA was isolated from liver tissue and analyzed as previously described. 42 The sequences of the primers used for quantitative PCR are given in Supplementary Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Immunoblot analysis was performed as previously described. 42 Anti-Bid (Cell Signaling, Boston, MA, USA) antibody was used in combination with appropriate peroxidase-conjugated secondary antibody. Protein load was verified with an actin antibody (dilution 1 : 10 000) (Santa Cruz, Dallas, TX, USA).…”
Section: Methodsmentioning
confidence: 99%
“…16,17 Recent study showed that pyroptotic cell death of hepatocyte mediated liver damage. 30 Another study showed that NLRP3 inflammasome activation contributed to the progression of non-alcoholic fatty liver disease. 31 Both of these reports contributed to our understanding of the pathogenesis of liver disease mediated by inflammasome activation.…”
mentioning
confidence: 99%